Guava fruit loss caused by rust - Maffia, Luiz Antônio; Silveira, Silvado Felipe da; Martins, Marlon Vagner Valentim (Summa Phytopathologica, 2014)
The aim of this paper was to estimate the loss caused by rust (Puccinia psidii) to 'Paluma' guava production in orchards located in Rio de Janeiro State. The disease intensity on the reproductive organs of plants was observed during two chemical control experiments carried out in 2003 and 2004. The loss was estimated based on simple linear regression and the production reduction (fruit number and weight ha-1) on the incidence of diseased buds and fruits. In the first experiment, no relationship was established between incidence of diseased buds and loss since there was a delay in spraying and the incidence of buds showing rust was high (mean of 47%) at the beginning of flowering. In the second experiment (2003-2004), spraying occurred at the beginning of the epidemics and there was a linear relationship between incidence of diseased buds and loss, justifying fungicide intervention at this stage. For the fruiting stage, a significant relationship was found between incidence of diseased fruits and loss in both experiments. In the absence of chemical control, rust reduced fruit production by around 90%.

Objetivou-se estimar os danos causados pela ferrugem (Puccinia psidii) à produção da goiabeira 'Paluma' em pomares localizados no estado do Rio de Janeiro. Intensidade de doença foi observada nos órgãos reprodutivos das plantas em dois experimentos de controle químico ocorrido em 2003 e 2004. Estimaram-se os danos através de regressão linear e a redução da produção (número e peso de frutos ha-1) em função da incidência de botões e frutos doentes. No primeiro experimento, não foi obtida relação entre incidência de botões doentes e dano devido ao atraso nas pulverizações e à alta incidência de botões com ferrugem (média de 47%) no início da floração. No segundo experimento (2003-2004) as pulverizações foram realizadas no início da epidemia e houve uma relação linear entre incidência de botões doentes e dano justificando a intervenção com fungicidas neste estádio. Para o estádio de frutos, foi obtida relação significante entre incidência de frutos doentes e dano em ambos os experimentos. Na ausência de controle, a ferrugem reduziu a produção de frutos em torno de 90%.
Keywords: Psidium guajava; Myrtaceae; Puccinia psidii